Ionic Flexible Sensors: Mechanisms, Materials, Structures, and Applications. (15th January 2022) - Zhao, Chun; Wang, Yanjie; Tang, Gangqiang; Ru, Jie; Zhu, Zicai; Li, Bo; Guo, Chuan Fei; Li, Lijie; Zhu, Denglin
Abstract: Over the past few decades, flexible sensors have been developed from the "electronic" level to the "iontronic" level, and gradually to the "ionic" level. Ionic flexible sensors (IFS) are one kind of advanced sensors that are based on the concept of ion migration. Compared to conventional electronic sensors, IFS can not only replicate the topological structures of human skin, but also are capable of achieving tactile perception functions similar to that of human skin, which provide effective tools and methods for narrowing the gap between conventional electronics and biological interfaces. In this review, the latest research and developments on several typical sensing mechanisms, compositions, structural design, and applications of IFS are comprehensively reviewed. Particularly, the development of novel ionic materials, structural designs, and biomimetic approaches has resulted in the development of a wide range of novel and exciting IFS, which can effectively sense pressure, strain, and humidity with high sensitivity and reliability, and exhibit self‐powered, self‐healing, biodegradability, and other properties of the human skin. Furthermore, the typical applications of IFS in artificial skin, human‐interactive technologies, wearable health monitors, and other related fields are reviewed. Finally, the perspectives on the current challenges and future directions of IFS are presented. Abstract : Ionic flexible sensors (IFS) represents one kind of advanced sensors based on ion migration. In this review, the latest developments of the fundamental working mechanism, latest matrix materials, unique electrodes, special structural designs, and newly enabled applications of IFS are entirely reviewed, expectedly providing a technical roadmap for the next wave of innovations and breakthroughs in this field.